HUBUNGAN DPRD DAN PEMERINTAH DAERAH DALAM PENETAPAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH - Melki, Melki (Kopertis Wilayah X, 2018)
The Regional Budget (APBD) is an annual financial plan developed by the regional government then discussed and agreed jointly by the local government and the Regional House of Representatives. This paper itself will discuss how the relationship of the Regional House of Representatives with the Regional Government in determining the APBD, using normative jurisdiction research. Law No. 9 of 2015 of the second amendment to Law No. 23 of 2014 on regional government states that local government administrators are local governments and DPRDs. Both local government institutions are elements of local government administration. The relationship between local government and DPRD in making regional regulation on APBD per, tends to deal in diametrically according to position, duty and authority. The local government and the DPRD jointly discuss and approve the draft local regulations. The draft local regulations on APBD initiatives and initiatives came from the local government, and the draft local regulations together with the DPRD discussed and approved the draft local regulations into local regulations.